Analisis Pengembalian Bantuan Dana Bergulir Melalui Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perkotaan di Kota Makassar (Studi Kasus BKM Maccini Salewangang Kelurahan Maccini Kecamatan Makassar) - Ramli, Anwar (Universitas Brawijaya, Indonesia, 2013)
The problem statements of this research were whether the factors of LAR, PAR, CCr, and ROI gave significant influence on aid fund repayment at BKM Maccini Salewangang PNPK Makassar, and which factor that influences the aid fund repayment dominantly. This research aims to analyze the role of LAR, PAR, CCr and ROI variables on aid fund repayment at BKM Maccini Salewangang, Makassar City as wellas to analyze the dominant variable which influences aid fund repayment at BKM Maccini Salewangang, Makassar City. The result reveals that the partial influence among LAR, PAR, CCr, and ROI variables on the aid fund repayment particularly at BKM Maccini Salewangang demonstrating that LAR and PAR variables give negative influence on the aid fund repayment as high LAR and PAR causes the aid fund repaymentbecome low. The result of the regression test indicates that the dominant variable which influences the aid fund repayment is ROI as the higher the ROI, results in more current aid fund repayment particularly at BKM Maccini Salewangang.